Orbital-accelerated transient simulations of glacial-interglacial climate cycles for the last 800,000 years - Baohuang Su; Yong Sun; Mengzi Zhou (Scientific Data)
Abstract Over the last 800,000 years, Earth’s climate has experienced periodic glacial and interglacial cycles driven by orbital parameters, CO2 concentrations, and ice sheet volumes. To understand how these climate forcing factors influence climate on orbital scales, high-resolution and continuous paleoclimate simulations are crucial. This study employed the CESM1.2.2 Earth System Model for four 800,000-year orbital-accelerated transient climate simulations, including a full-forcing experiment and three single-factor forcing experiments. The results were compared with geological proxy records from various regions, showing good agreement in mid-low latitude monsoon systems, mid-latitude sea surface temperatures, and high-latitude North Atlantic climate variability. However, the model underestimated sea surface temperature fluctuations in the tropics and Southern Hemisphere mid-latitudes. Despite this, it accurately depicted high-latitude climate characteristics. These climate simulation datasets include global annual mean surface temperature and precipitation distributions with a horizontal resolution of 3.75°. Overall, these simulations provide a reliable and verifiable climate dataset, offering strong support for studying the driving mechanisms of past glacial-interglacial climate changes and interpreting long-term climate signals in geological records.